PENERAPAN FRAMEWORK LARAVEL PADA SISTEM INFORMASI PEMINJAMAN ALAT DAN BAHAN DI LABORATORIUM PERGURUAN TINGGI - Ihsan; Lesmideyarti, Dwi; Armin (PPPM POLTESA, 2023)
The message is the development of technology and information. This affects how easily a particular job can be done quickly and efficiently. This includes managing goods and providing tools and materials needed by an agency to carry out operational activities. Stating the purpose of this system is very important. Especially at Balikpapan State Polytechnic, because the data collection method is still manual, by hand writing on loan forms and visits to campus to check whether items are available or not. This can be said to be ineffective and inefficient in supporting work productivity.Therefore, it is recommended that the Electrical Engineering Department of the Balikpapan State Polytechnic create an information system for borrowing equipment and supplies. In this system the method used is Waterfall. Laravel functions as a framework and MySQL functions as a database for the information system being developed.The results of this research can work well whenever and wherever they are accessed. Students and laboratory staff can use a web browser on their respective devices connected to the internet network to access this system. By using this system the Electrical Engineering Department can manage tools and materials more effectively and efficiently.